Thyroid disorders in women with dysfunctional uterine bleeding (Journal of Pathology of Nepal, 2016)
Background: Thyroid hormones play a key role in the menstrual and reproductive function of women .It is recognized universally that menstrual disturbances may accompany clinical alteration in thyroid function and every clinician has encountered altered menstrual pattern among women suffering from thyroid disorders. The aim of this study was to find the incidence of thyroid disorders in Dysfunctional uterine bleeding and its correlation with menstrual patterns.Materials and Methods: A hospital based cross-sectional study including 75 cases with dysfunctional uterine bleeding attending the OPD of Nobel Medical College, where incidence of thyroid disorder was evaluated along with its correlation with menstrual patterns and histopathology.Results: The incidence of Gynecological OPD attendance due to abnormal uterine bleeding was 3%.and the incidence of thyroid dysfunction was 10.6% with hypothyroidism being the commonest. (9.3%). The commonest menstrual pattern found was menorrhagia/polymenorrhoea in 8 percent.Conclusion: Prevalence of hypothyroidism was more common in DUB. Thus every woman with menstrual irregularities should undergo thyroid assessment and this will ultimately avoid unnecessary intervention like misuse of hormonal treatment and hysterectomy.